If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5x + -49 = 113 Reorder the terms: -49 + -5x = 113 Solving -49 + -5x = 113 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '49' to each side of the equation. -49 + 49 + -5x = 113 + 49 Combine like terms: -49 + 49 = 0 0 + -5x = 113 + 49 -5x = 113 + 49 Combine like terms: 113 + 49 = 162 -5x = 162 Divide each side by '-5'. x = -32.4 Simplifying x = -32.4
| 3t-14=2t+10 | | 6.1=-9+x | | 8x*4+4=68 | | x=81/(9(10-1)) | | 2(x+2.50)=16.00 | | X-2=3.7 | | 6a-54=5a+25 | | 1+3n=8+2n | | 12x3/9y8= | | x=81/9(10-1) | | 7.0-3x=1 | | X*2+1=3x+11 | | 5(3x+6)+4=15x+34 | | 2/7x=56 | | 20a*48a= | | 4y+7=4y-6 | | c+19.1=12.1 | | 3(n+1)=6n-9 | | X+3=-2x+12 | | 20a+48a= | | L+21=(-l)+87 | | v/4--10=13 | | |cos(x-pi/4)|=rad2/2 | | 5m-4+3m=24 | | z/3=1.49 | | 8x=17x-3 | | 7w+4-2=6w+4 | | 13=2j+5 | | -3p+9=-6 | | -8m+4=-44 | | 2+-3g=5 | | y/6-6=6 |